Digital journalism - Jones, Janet; Salter, Lee (SAGE, 2012)
Overview: how can we make sense of the ongoing technological changes affecting journalism and journalists today? Will the new digital generation break down barriers for journalism or will things just stay the same? These and other pertinent questions will be asked and explored throughout this exciting new book that looks at the changing dynamics of journalism in a digital era. Examining issues and debates through cultural, social, political and economic frameworks, the book gets a grip on today's new journalism by understanding its historical threats and remembering its continuing resilience and ability to change with the times. In considering new forms of journalistic practice the book covers important topics such as: truth in the new journalism, the changing identity of the journalist, the economic implications for the industry, the impact on the relationship between the journalist and their audience, and the legal framework of doing journalism online